Penerapan Metode Failure Mode and Effects Analysis dan Reliability Centered Maintance dalam Optimasi Sistem Maintance pada Mesin Sterilizer di PT. Perkebunan Nusantara IV Regional II Unit Kebun Sawit Adolina - Widya Fernanda Putri; David Juan Abelio Pardede; Anita Sari Sihotang (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The high frequency of downtime and recurring failures of critical components in the sterilizer machine at PT Perkebunan Nusantara IV Regional II, Kebun and PKS Adolina Unit, indicates that the current maintenance system is not running optimally and is still dominated by corrective maintenance. This study aims to analyze and optimize the sterilizer machine's maintenance system through the application of the Failure Mode and Effect Analysis (FMEA) and Reliability Centered Maintenance (RCM) methods. The FMEA method is used to identify failure modes, their causes, and determine the risk priority level based on the Risk Priority Number (RPN). Furthermore, the RCM method is applied to determine the most appropriate maintenance strategy based on component functions and their failure consequences. This study uses a quantitative descriptive approach with a case study on the sterilizer machine at PKS Adolina, utilizing data obtained from field observations, interviews, and the company's historical data. The data analysis techniques include calculating the RPN value to determine critical components in FMEA, and performing the RCM decision logic analysis. The results show that the primary critical component failures are leakage in the exhaust packing, followed by the sterilizer door packing, and the condensate switch. The application of the RCM method generates recommendations for maintenance strategies in the form of preventive maintenance, predictive maintenance, and failure-finding maintenance. By implementing these strategies, it is expected that the downtime of the sterilizer machine can be minimized and machine reliability can be enhanced sustainably.